The Application of Modified Gasing Game to Improve the Elementary School Students’ Vocabulary in Singkawang Tourism Site, West Kalimantan - Ufi Ruhama; Iin Maulina (Universitas Ahmad Dahlan, 2020)
This Classroom Action Research was aimed at knowing whether the implementation of modified gasing game was effective in improving students' vocabulary mastery. The population in this study was the students of Muhammadiyah 2 Singkawang Elementary School with a total sample of 25 students by using a random sampling technique. The Classroom Action Research objectives were to describe the use of a modified-gasing game on vocabulary, to investigate the Muhammadiyah 2 Singkawang Elementary School fourth grade students’ vocabulary mastery and to identify the improvement of the Elementary School fourth grade students’ vocabulary mastery using a modified-gasing game. It employed three cycles with four stages (planning, action, observation, and reflection). In each cycle, the data were analyzed to find out the increase in students’ vocabulary. The researcher used the observation, test and documentation in collecting the data. The results of the research indicated that the implementation of gasing game was merely effective in improving the students’ vocabulary in terms of numerical grade scores. The results showed the improvement in each cycle as in the first cycle by 0 percent, in the second cycle by 48 percent, and in the third cycle by 96 percent which are categorized very good. The results concluded that this modified-gasing game can improve the Muhammadiyah 2 Singkawang Elementary School fourth grade students’ vocabulary significantly in the aspects of word guessing.